Endosulfan exposure reduced fertilization, hatching, and survival rate of the lemon fin barb hybrid eggs and larvae - Mohd Nazri, Muhammad Nur Fikri; Mazlan, Mazlina; Ismail, Muhammad Fadhil Syukri; Mohd Zohdi, Rozaini; Awang Junaidi, Awang Hazmi (Egyptian Society for Animal Management (ESAM), 2025)
Endosulfan (ES) is an organochlorine insecticide that has been extensively used in agricultural production. Despite being banned globally, the production and illegal use of ES continue in certain countries, raising concerns about their impact on the environment and human health. The aim of this study was to examine the effect of ES on the fertilization, hatching, and survival rate of the lemon fin barb hybrid (LFBH; Hypsibarbus wetmorei × Barbonymus schwanenfeldii) eggs and larvae. A pair of LFBH was used as the broodstock. The sperm and eggs harvested via the stripping method were mixed and exposed to different concentrations of ES (0 ppm, or control; 0.01 ppm, 0.1 ppm, or 1 ppm). The fertilization and hatching rates were evaluated in vitro at 3 and 18 hours post-exposure, respectively. The survival rate of the larvae was assessed at 24, 48, and 72 hours post-hatching. The fertilization and hatching rates of the LFBH eggs treated with 1 ppm ES (44.24±4.6% and 18.54±2.8%, respectively) were significantly lower (p<0.05) than the control (63.35±5.8% and 46.76±1.3%, respectively). The main effect of treatment and time on the survival rate of the larvae was significant (p < 0.019) within three days post-hatchlings, where the survival rate of larvae exposed to 1 ppm was significantly lower (p < 0.05) than the control at every time interval. Overall, ES exposures displayed a detrimental effect on the early development and survival of the LFBH eggs and larvae.